Cytomegalovirus antiviral stewardship in solid organ transplant recipients: A new gold standard. Issue 5 (18th October 2022) - Jorgenson, Margaret R.; Descourouez, Jillian L.; Kleiboeker, Hanna; Goldrosen, Kerry; Schulz, Lucas; Rice, John P.; Odorico, Jon S.; Mandelbrot, Didier A.; Smith, Jeannina A.; Saddler, Christopher M.
Abstract: Purpose: Antimicrobial stewardship programs (ASPs) are essential entities that promote the appropriate use of antimicrobials, leading to improved patient outcomes and reduced resistance. Application to the immunocompromised host is a natural progression for expansion. Cytomegalovirus (CMV) infection is a common complication following solid organ transplant with significant implications on graft survival, making it an attractive ASP target. The aim of this piece is to review our center‐specific experience with the development, implementation, and maintenance of a CMV stewardship initiative at a large transplant center. Methods: Our CMV stewardship initiative began in 2018. Herein, we review 3 years' experience and quality‐related improvement that occurred from initiation to present state and share our stewardship algorithms. Special attention is paid to the impact of the program as well as our increased understanding of the complex interplay between prevention, treatment, and host development of CMV‐specific cell‐mediated immunity (CMI). Results: We found our stewardship initiative not only reduced the incidence of ganciclovir resistance but also streamlined care via a centralized and structured approach. This objective, protocolized program has resulted in a significant shift away from a reactive to a proactive state and in turn, reduced CMV treatment rates (26% at initiation to 12% in the current state, p  = .012). Conclusion: A dedicated multidisciplinary team focused on CMV stewardship is imperative in providing a patient‐centered approach focused on development of CMV‐specific CMI, and as a result prevention of CMV disease. We believe these programs will be the new gold standard for CMV management.